Oral dysbiosis and systemic diseases - Georges, F. M.; Do, N. T.; Seleem, D. (Frontiers in Dental Medicine, 2022)
The aim of this mini review is to investigate the connection between oral microbiome dysbiosis and systemic diseases. Many systemic conditions can have oral manifestations and cause worsening in oral diseases. For example, uncontrolled type 2 diabetes has been associated with worsening of periodontal disease. Other inflammatory diseases or autoimmune diseases may predispose to oral mucositis, mucosal ulcers, xerostomia, and higher susceptibility to oral infections. This review will outline common systemic diseases, such as metabolic, cardiovascular, and immunologic disorders as they relate to oral manifestations and changes in the oral microbiome composition.